MESIN PEMBAKARAN PIROLISIS BERBAHAN DASAR SEKAM PADI DAN SABUT KELAPA PENGHASIL ASAP CAIR (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2022)
This study aims to obtain smoke gas through pyrolysis technology by processing biomass materials around us, as well as knowing the effect of increasing the pyrolysator temperature on the capacity of the smoke gas produced and the content in the biomass smoke gas. The combustion process in the combustion tube uses the pyrolysis method or combustion with low oxygen levels or does not use oxygen. This second concept uses additional distillation methods to improve the quality of the liquid smoke produced. The third product concept has a combined design of the two previous concepts. This third concept uses the concept of three phase changes using two condenser tubes and one distillation tube.